The Role of Organizational Citizenship Behavior in Improving Job Quality in (School Feeding and Humanitarian Relief Project) (SFHRP) - Al-Hawsli, AbdulKarim Dahan Saleh Ali; Tawwaf, Abdulkhaleq Hadi (Journal of Economic, Administrative and Legal Sciences, 2025)
The importance of the study lies in exploring the role of organizational citizenship behaviour in improving job satisfaction at SFHRP through the perspective of the employees, drawing the attention of stakeholders to the role of humanitarian organizations in Yemen over the past decade. Humanitarian organizations face many problems in the internal work environment, such as low motivation, weak internal communication, low morale among employees, and increased turnover rates. The study revealed the role of citizenship behaviours as a fundamental factor in enhancing job quality. The study used the descriptive analytical method to answer the study questions and test the hypotheses. The study population consisted of employees of the SFHRP. The sample was a non-proportional stratified random sample of 500 individuals, with 335 responding, which is 68%. Study results: It shows a high level of organizational citizenship behaviours, with a verbal significance indicating it was high, with a mean of (4.26) and a standard deviation of (0.490). There was a moderate level of work-life quality practices, with a mean of (3.062) and a standard deviation of (0.649). The hypothesis testing results showed that the direct impact of organizational citizenship behaviour on improving work-life quality was statistically significant. The study concluded that it is necessary to maintain a high level of organizational citizenship behaviour and to enhance the level of work-life quality, especially the balance between personal life and work.
Keywords: Organizational Citizenship Behavior; Quality of Work Life